Characterizing Interactions of Ionic Liquid Based Electrolytes with Electrospun Gas Diffusion Electrode Frameworks by 1H PFG NMR - Merz, Steffen; Jakes, Peter; Tempel, Hermann; Weinrich, Henning; Kungl, Hans; Eichel, Rüdiger-A.; Granwehr, Josef (Diffusion Fundamentals, 2017)
Pulsed field gradient (PFG) 1H NMR was used to characterize the mobility of ionic liquid cations in porous gas diffusion electrode (GDE) frameworks for metal–air electrochemical systems. The carbon GDE frameworks were produced by electrospinning. It was found that the motion of ionic liquids in the highly porous hosts is more complex than what is commonly exhibited by conventional fluids, which makes a multimodal investigation essential for an adequate description of mobility and wetting of GDEs. Observed NMR diffraction-like patterns cannot be linked to the tortuosity limit but may serve as a proxy for structural features in the fibrous material. While the observed data were interpreted using standard theoretical models, alternative explanations and causes for artifacts are discussed.